PENGARUH DISIPLIN DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT ATLAS RESOURCES TBK JAKARTA - Asep Maulana Sidik; Anggada Bayu Seta (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the effect of discipline and punishment on employee performance at PT Atlas Resources Tbk Jakarta. The research method used is a quantitative descriptive approach with simple and multiple linear regression analysis. Data were obtained through questionnaires filled out by 58 company employee respondents. The results of the study indicate that work discipline has a positive and significant effect on employee performance with a contribution of 53.1%. This is evidenced by the results of the hypothesis test analysis which shows the t_count value> t_table, namely 7.916> 1.672 with a p-value <0.05 or 0.000 <0.05. On the other hand, punishment partially does not have a significant effect on employee performance, although it has a strong correlation. This is evidenced by the results of the hypothesis test analysis which shows the t_count value <t_table, namely -0.587 <1.672 with a p-value of 0.560> 0.05. However, simultaneously, discipline and punishment have a significant effect on employee performance with a contribution of 53.1%. This is proven by the results of the F-test analysis which shows the value of F_count > F_table, namely 31.111 > 3.160 with a significance level of 0.000 < 0.05. Based on the results of the study, increasing work discipline can encourage employee performance, while the punishment applied does not always have a significant impact on improving performance.